(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In this article the structural-morphological structure, their etymological foundations, affection system, semantic motivation and historical and linguistic layers of the toponyms of the Kashkadarya oasis are analyzed. The study reveals the mechanism of formation of morphological models under the example of toponyms that reveal the multilayer history of the language history, ethnic composition and landscape features of the Kashkadarya region. The results obtained serve to determine the typological, linguistic and historical consistency of the toponymy of the region.